Un acercamiento teórico a la economía digital como alternativa de recuperación pospandemia en Latinoamérica (Tema Central) - Armijos Orellana, Ana Carolina (2023)
The COVID-19 pandemic caused an unprecedented change in the social-economic environment worldwide, speeding up even more the establishment and dissemination of digital economy. The objective of this research is to describe and identify the main characteristics, benefits and obstacles of the digital economy in Latin America. Using a bibliographical review using an analytic-synthetic method, it was determined that digital economy may bring structural changes, diminish inequality and encourage social inclusion processes, as well as promote construction and participative development of organizational structures and institutional capacities in Latin American countries. The results proved that digital economy is still in early stages in this region and that at least three factors are necessary for it to be properly established: a relation of cooperation and interdependency between Academia-Companies-State; digital literacy and the establishment of public and private policies ensuring an adequate environment to allow for dynamic, sustainable social-economic growth.